Low Catalyst Loading in the Cross Metathesis of Olefins with Methyl Vinyl Ketone - Abbas, Muddasar; Leitgeb, Anita; Slugovc, Christian (Synlett, 2013)
An olefin-metathesis catalyst featuring a 1,3-bis(2,6-diisopropylphenyl)-4,5-dihydroimidazol-2-ylidene N-heterocyclic carbene and an ester-chelating carbene ligand efficiently promoted the cross metathesis of olefins with 3-buten-2-one in the presence of copper iodide as cocatalyst. At optimized reaction conditions a 10–20 times lower catalyst loading compared to the state of the art could be achieved.
Keywords: catalysis; metathesis; enones; alkenes; ruthenium